Extracorporeal Membrane Oxygenation (ECMO) Support in Special Patient Populations—The Bidirectional Glenn and Fontan Circulations - Bacon, Matthew K.; Gray, Seth B.; Schwartz, Steven M.; Cooper, David S. (Frontiers in Pediatrics, 2018)
Extracorporeal membrane oxygenation (ECMO) is a support modality used within the pediatric cardiac ICU population as a bridge to recovery or decision in the setting of acute myocardial decompensation, support for combined cardiopulmonary failure or in the setting of refractory cardiopulmonary arrest. Patients with univentricular physiology are at particular risk for decompensation requiring ECMO support. This review will focus upon current evidence and techniques for ECMO support of single ventricle patients who have undergone a stage II bidirectional Glenn procedure or the stage III Fontan procedure.